The Treatment of Bankruptcy Between Penal and Civil Matters; Legal Based on The Hammurabi Code, The Bible, and The Sunnah - Rusydianta, Muhammad; Rachmawati, Andini; Affandi, Muchammad Taufiq (Suhuf: International Journal of Islamic Studies, 2026)
Background: This article addresses gaps in existing literature by re-examining the historical foundations and origins of bankruptcy law across different eras. Objective: It aims to reveal the evolution of bankruptcy treatment from the Babylonian period to the Prophetic tradition (Sunnah) as understood by the fuqaha’. Methodology: Utilizing a legal-semiotics-to-statute approach, this research qualitatively analyzes legal materials to provide a descriptive explanation of how bankruptcy concepts developed. Results: The findings show that bankruptcy in ancient times and early European states functioned primarily as a conflict-resolution tool within civil-penal systems. While the Bible transitioned bankruptcy into a civil matter specifically for the children of Israel, the Sunnah (since the 7th century) integrated both civil and penal aspects without criminalizing the state of bankruptcy itself. Conclusion: Bankruptcy treatment in the Hammurabi Code, the Bible, and the Sunnah consistently fluctuates between penal and civil realms, yet each possesses distinct characteristics. Notably, prophetic and divine values within ahkam iflas have conjecturally been absorbed into Western legal culture since the Middle Ages. This study fosters a deeper understanding of prophetic law and its historical legal transplantation, highlighting its convergence with modern bankruptcy frameworks.